Produção de textos narrativos com enfoque na habilidade metatextual: programa de intervenção para o 5º ano do Ensino Fundamental - Dias, Luiz Carlos (2020)
Knowing how to read and write are fundamental skills and, in a way, indispensable for individuals from a literate culture. Having full command of the alphabetic system implies decoding and understanding what is written. This learning, in turn, allows direct access to standards and other information, and at the same time, the independence of interpreters. Therefore, with the inclusion of children in the schooling process, it is no coincidence that learning written language is one of the first to be performed, as it allows access to other learning at school. This is an experimental research with control group, designed in three stages: pretest, intervention and post-test and aimed to verify the effect of instructions regarding narrative schemes on the production of texts in real teaching conditions. Fifty-nine children from two 5th grade elementary school students from a public school in São Paulo participated in the research. By lot, it was defined that the 5th year A would be the intervention and that the 5th year B would be the control. The pre-test consisted of a narrative text production with the theme “The Great Adventure” and, after its evaluation, 34 texts were considered in the “alphabetic with proficiency” category, 17 of the 5th grade A and 17 of the 5th grade B. Although the sample consisted of 17 children, the intervention activities were performed with all 29 children present in the classroom of the 5th grade class A (Experimental Group). The 30 children from the 5th grade B class, to which the participants of the control group belonged, followed with the regular pedagogical activities. The intervention sessions consisted of metatextual activities: scrambled games, explicit marking of parts of the text, puzzles. The post-test results indicate that after the six intervention sessions, there was a significant change in the production of written texts in favor of children in the 5th grade (Experimental Group). It was concluded that the average grade increase in the experimental group is higher than the average grade increase in the control group